Correlation Self-Compassion and Stress in Patients with Type II Diabetes Mellitus - Ledia Restipa; Hidayatul Rahmi (Journal of Health Sciences and Epidemiology, 2023)
Type 2 diabetes mellitus (T2D) in the elderly is an increasing health problem. Elderly patients with type 2 diabetes have a higher risk of diabetes complications and require appropriate treatment. This disease causes 4 million deaths annually, accounting for 9 percent of all deaths worldwide. The purpose of the study was to assess the correlation of self-compassion and stress on T2D patients at the Lubuk Buaya Health Center. This study used a cross- sectional study design. 85 elderly people with T2D referring to the Lubuk Buaya Health Center were enrolled through a simple randomized sampling method from November to February 2022. In order to collect data, the Depression Anxiety Stress Scales (DASS) and  the self-compassion scale (SCS) were used. In addition, to analyze the data, pearson product moment test methods were done using SPSS V.22 software. The results show that there is a significant correlation between self-compassion and stress in patients T2D. Self-compassion is one of the most effective methods for reducing stress in diabetic patients. Consequently, therapists, counselors, and psychologists are encouraged to employ self-compassion training to reduce stress in T2D patients. Keywords: Diabetes Melitus, Type II, Stress, Self-Compassion